Extracellular matrix remodeling of the testes through the male reproductive cycle in Teleostei fish - Oliveira Santana, Julio Cesar de [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Springer, 2014)
During the fish reproductive cycle, testes undergo morphological changes related to germinal epithelium and remodeling of extracellular matrix components (ECM). ECM is degraded mainly by action of matrix metalloproteinases (MMPs). Due to the natural renewal of ECM in fish testes, we choose Pimelodus maculatus to study remodeling of ECM throughout reproductive cycle, using picrosirius (to identify type I, II, III collagen) and reticulin (type III collagen), and to immunolocalize MT1-MMP (membrane type 1-matrix metalloproteinase) and MMP-2 in testis cells. Testes were classified in four reproductive phases: regenerating, development, spawning capable and regressing. Picrosirius and reticulin demonstrated a differential distribution of total collagen fibers during the reproductive cycle. Immunohistochemistry showed MT1-MMP only in acidophilic granulocyte cells mainly inside blood vessels, in connective tissue of capsule close to the germinal compartment, and also infiltrated in interstitial connective tissue. MMP-2 was detected in fibroblast and endothelial cells of interstitial and capsule blood vessels, in epithelial cells of capsule, and in acidophilic granulocyte cells at same description for MT1-MMP. The fish testes ECM were remodeled throughout reproductive cycle in according to morphophysiological alterations. During reproductive season (spawning capable), the interstitium increased in total collagen fibers (type I, II, III). After spermiation period (regression and regenerating), the amount of collagen fibers decreased in response to action of MMPs on collagen degradation and other interstitial components (not assessed in this study). MMPs seem to be indispensable components for natural cyclic events of ECM remodeling of fish testes and for guarantee tissue homeostasis throughout reproductive cycle.
Keywords: Reticulin; Picrosirius; Collagen; MMP; Acidophilic granulocyte cell